PERBEDAAN HASIL BELAJAR MATEMATIKA ANTARA SISWA YANG DIAJAR MENGGUNAKAN MODEL PEMBELAJARAN LANGSUNG DAN DISCOVERY LEARNING PADA SISWA KELAS VII SMP NEGERI 14 SIGI: Differences In Mathematics Learning Outcomes Between Students Taught Using Direct Learning Model and Discovery Learning In Class VII Student at SMP Negeri 14 Sigi - Kirana, Ranita Candra; Rizal, Muh. (Aksioma, 2024)
This research aims to determine the difference in improving learning outcomes between students taught using the direct learning model and students taught using the Discovery learning model. The research method used was quasi experimental design. The population in this study were class VII students at SMP Negeri 14 Sigi in the even semester 2023/2024 and 2 classes were chosen as experimental research classes. The research was carried out by giving two different treatments to two groups of students. First, experimental class I received teaching using a direct learning model, then experimental class II used a discovery learning model. Data collection was carried out by giving tests to students at the beginning and end of the research. The research results show that there is a significant difference in improving the learning outcomes of students who are taught using the direct learning model and students who are taught using the discovery learning model.